The IN-PANCIA Study: Clinical Evaluation of Gastrointestinal Dysfunction and Failure, Multiple Organ Failure, and Levels of Citrulline in Critically Ill Patients. (March 2020) - Fagoni, Nazzareno; Piva, Simone; Marino, Rosella; Chiarini, Giovanni; Ferrari, Daniela; Grespi, Eleonora; Bertuetti, Rita; Barbieri, Silvia; Latronico, Nicola; Rasulo, Frank
Purpose: Gastrointestinal dysfunction and failure (GID and GIF) in critically ill patients are a common, relevant, and underestimated complications in ICU patients. The aims of this study were (1) to determine plasmatic levels of citrulline, glutamine, and arginine as markers of GID/GIF in critically ill patients with or without GID/GIF with or without multiple organ failure (MOF) and (2) to assess the role of intra-abdominal hypertension in these patient groups. Materials and Methods: This is a 1-year, monocentric (Italian hospital), prospective observational study. Inclusion criteria were adult patients with GID/GIF, with or without MOF. The GIF score was daily evaluated in 39 critically ill patients. Amino acids were measured at the time of GID or GIF. Results: We enrolled 39 patients. Nine patients developed GID and 7 GIF; 6 of patients with GID/GIF developed MOF. Citrulline was lower ( P < .001) in patients with GID/GIF (11.3 [4.4] µmol/L), compared to patients without GID/GIF (22.4 [6.8] µmol/L); likewise, glutamine was lower in patients with GID/GIF, whereas arginine was nonstatistically different between the 2 groups. Intra-abdominal pressure was higher in patients affected by MOF (13.0 [2.2] mm Hg) than in patients with GIF/GID without MOF (9.6 [2.6] mm Hg) and compared to patients without GID/GIF (7.2 [2.1] mm Hg). Conclusions: Both GID and GIF in critically ill patients are associated with low levels of citrulline and glutamine, which could be considered as markers of small bowel dysfunction. The higher the GIF score, the lower the citrulline levels. Patients affected by MOF had higher levels of intra-abdominal pressure.